Global technology cycles and local economic performance - Sebastian Heinrich; Samad Sarferaz; Martin Wörter (ETH Zurich, KOF Swiss Economic Institute, 2023)
This paper studies the global synchronicity of technology and its impact on the economy. We employ dynamic factor analysis to decompose patent data in different digital technologies for various countries into global and country-specific factors. Our findings confirm the existence of global and local technology cycles. We further find a significant positive correlation between the estimated global technology index and a country's economic performance. This positive effect is stronger in countries with broad technological exposure. However, a concentration in only few dominant technological fields seems to reduce the positive impact of the global technology cycle on a country's economic performance.
hdl:20.500.11850/611531
Keywords: O31; O33; O47; C38; L86; 330; innovation index; dynamic factor model; patent data; productivity growth; knowledge diffusion; digitalization; globalization